Effects of L-citrulline supplementation on blood pressure: A systematic review and meta-analysis - Bahareh Barkhidarian; Masoud Khorshidi; Sakineh Shab-bidar; Baran Hashemi (Mashhad University of Medical Sciences, 2019)
Objective: We aimed to conduct a systematic review and meta-analysis of clinical trials that examined the effects of L-citrulline supplementation on blood pressure (BP).  Materials and Methods: We searched MEDLINE, SCOPUS, PUBMED and Google scholar databases from inception to November 16, 2017 and 811 papers were identified, of which 8 trials with 10 data sets met the inclusion criteria. Inclusion criteria were: (1) application of randomized clinical trial with either crossover or parallel designs; (2) studies conducted in adults (≥18 y); (3) oral supplementation with L-citrulline compared to control group; (4) expression of sufficient data about systolic and diastolic BP at baseline and at the end of the study in each group. BP effects were pooled by random-effects models, with trials weighted by inverse variance. Results: The included studies' sample size ranged between 12 and 34 subjects. The mean age of the participants in these trials ranged between 22 and 71 years. Dosage of L-citrulline supplementation varied from 3 to 9 g/day. Duration of the intervention ranged between 1 and 17 weeks. The pooled changes in systolic and diastolic BP were (MD, −4.10 mm Hg; 95% CI [−7.94, -0.26]; p=0.037) and (MD −2.08 mm Hg; 95% CI [−4.32, 0.16]; P=0.069), respectively. The subgroup analysis showed a significant diastolic BP reduction in studies that used doses of ≥6 g/day (MD −2.75 mm Hg; 95% CI [−5.37, -0.12]; p=0.04). Conclusion: Our results suggest that L-citrulline supplementation may reduce systolic BP. A significant reduction in diastolic BP was observed only in the studies that used doses ≥ 6 g/day.